Anthropometric and metabolic parameters in relation to high sensitivity C-reactive protein in Montenegrin population with type 2 diabetes: CRP in type 2 diabetes - Scepanovic, Andjelka; Medin, Darko; Vujovic, Slavica; Kavaric, Nebojsa; Klisic, Aleksandra (Progress in Nutrition, 2019)
Background/Aim: High sensitivity C-reactive protein (hsCRP) in widely recognized inflammation marker associated with increased cardiovascular disease (CVD) risk. Since CVD is a common complication in type 2 diabetes (DM2), and since there is a high prevalence of obesity and DM2 in Montenegro, we aimed to examine the association of hsCRP with anthropometric and metabolic parameters in the cohort of individuals with DM2. Additionally, we aimed to examine the gender difference in CVD risk as determined with hsCRP levels. Methods: A total of 184 participants with DM2 (of them 47.3% females) were recruited in this cross-sectional study. Fasting glucose, glycated hemoglobin, lipid parameters and hsCRP were measured. Anthropometric parameters were obtained. Participants were stratified into low (hsCRP